Influence of interleukin-6 gene polymorphism on the efficacy of antiviral treatment in patients with chronic hepatitis C - Riabokon, Yu. Yu.; Kalashnyk, K. V.; Riabokon, O. V.; Рябоконь, Юрій Юрійович; Калашник, Кирило Вадимович; Рябоконь, Олена Вячеславівна; Рябоконь, Ю. Ю.; Калашник, К. В.; Рябоконь, Е. В. (Запорізький державний медичний університет, 2019)
Aim. The aim of the work was to determine the influence of interleukin-6 gene polymorphism on the effectiveness of antiviral therapy in patients with chronic hepatitis C. Materials and methods. A total of 83 patients with chronic hepatitis C (CHC). were included in the study. The efficacy of therapy with the peg-IFNα + SOF + RBV was analyzed depending on the polymorphism of interleukin-6 gene (rs1800795). Results. All CHC patients with the CC genotype (14 – 100 %) responded to antiviral therapy with the peg-IFNα + RBV + SOF, but only 85.5 % of the patients with CG/GG genotypes responded (59 of the 69). In CHC patients with CG/GG genotypes, who responded to the therapy by SVR 24 formation, the HCV-RNA negativization was slower, in contrast to patients with the CC genotype, who showed a persistent absence of the virus in the blood from the 4th week of treatment. All patients with the CC genotype of IL-6 gene polymorphism presented complete normalization of ALT activity at this time if SVR 24 had been achieved. In the vast majority of CHC patients with SVR 24 and the CG/GG genotype after the therapy cessation, ALT activity continued to decrease and normalized after 24 weeks of observation in 94.9 % (56 of the 59). However, 20.0 % of patients with the CG/GG genotype who did not respond with the formation of SVR 24, had elevated serum ALT activity at the time of SVR 24 evaluation. Kendall’s rank correlation was performed to determine the factors, which statistically significantly affect the results of peg- IFNα + RBV + SOF therapy. IL-6 gene polymorphism had an effect on the efficacy of therapy, both on the HCV-RNA negativization in the blood at the end of treatment (P = 0.04) and on the achievement of SVR 24 (P = 0.03). The lack of response as well as the lack of SVR 12 and SVR 24 formation at the time of therapy completion were associated with the IL-6 gene CG/GG polymorphism presence and a higher index of ALT activity at the beginning of treatment (τ = -0,18, P < 0.01). Conclusions. In CHC patients, the CC genotype of IL-6 gene (rs1800795) is a favorable prognostic factor for the formation of SVR 24 in the treatment of peg-IFNα + RBV + SOF. Patients who did not respond to the treatment by SVR 24 formation had only the IL-6 gene CG/GG polymorphism. Even in HCV patients with CG/GG genotypes who responded to the treatment by SVR 24 formation, the negativization of HCV-RNA in the blood was slower, unlike the patients with CC genotype. The absence of response at the time of therapy completion, as well as the absence of SVR 12 and SVR 24, were associated with the presence of the IL-6 gene CG/GG polymorphism and a higher level of ALT activity at the beginning of therapy (τ = -0,18, P < 0.01). Мета роботи – визначити вплив поліморфізму гена інтерлейкіна-6 на ефективність противірусної терапії хворих на хронічний гепатит С. Матеріали та методи. У дослідження залучили 83 особи, які хворі на хронічний гепатит С (ХГС). Виконали аналіз ефективності противірусної терапії за схемою peg-IFNα + SOF + RBV залежно від поліморфізму гена інтерлейкіна-6 (rs1800795). Результати. Встановили, що всі хворі на ХГС із генотипом CC (14 – 100 %) відповіли на противірусну терапію за схемою peg-IFNα + RBV + SOF, але серед пацієнтів із генотипами CG/GG відповіли на лікування тільки 85,5 % (59 із 69). У хворих на ХГС із генотипами CG/GG, які відповіли на ПВТ формуванням СВВ 24, негативація HCV-RNA у крові відбувалася повільніше, на відміну від пацієнтів із генотипами СС, в яких від 4 тижня лікування відзначено стійке зникнення вірусу. За умов досягнення СВВ 24 у всіх хворих із генотипом СС поліморфізму гена ІЛ-6 у цей термін спостереження відбулася нормалізація активності АлАТ. Здебільшого у хворих на ХГС із СВВ 24 та CG/GG генотипом після припинення ПВТ активність АлАТ продовжувала знижуватися та нормалізувалася через 24 тижні спостереження у 94,9 % (56 із 59). Але у 20,0 % пацієнтів, які не відповіли формуванням СВВ 24 та мали генотипи CG/GG, на момент оцінювання СВВ 24 активність АлАТ у сироватці крові залишилася підвищеною. Для визначення факторів, які мають статистично значущий вплив на результати ПВТ за схемою peg-IFNα + SOF + RBV, здійснили рангову кореляцію за Кенделом. Поліморфізм гена ІЛ-6 мав вплив на ефективність ПВТ: як на негативацію HCV-RNA у крові на момент завершення лікування (р = 0,04), так і досягнення СВВ 24 (р = 0,03). Відсутність формування відповіді на момент завершення ПВТ, а також відсутність формування СВВ 12 і СВВ 24 асоціювалися з наявністю генотипів CG/GG поліморфізму гена ІЛ-6 і вищим рівнем активності АлАТ до початку ПВТ (τ = -0,18, р < 0,01). Висновки. У хворих на ХГС генотип СС поліморфізму гена ІЛ-6 (rs1800795) є прогностично сприятливим щодо формування СВВ 24 під час проведення ПВТ за схемою peg-IFNα+SOF+RBV. Пацієнти, які не відповіли на лікування СВВ 24, мали тільки генотипи CG/GG поліморфізму ІЛ-6. Навіть і у хворих на ХГС із генотипами CG/GG, які відповіли на ПВТ формуванням СВВ 24, негативація HCV-RNA у крові відбувалася повільніше, на відміну від пацієнтів із генотипами СС. Відсутність формування відповіді на момент завершення ПВТ, а також відсутність СВВ 12 і СВВ 24 асоціювалися з наявністю генотипів CG/GG поліморфізму гена ІЛ-6 і вищим рівнем активності АлАТ до початку проведення ПВТ (τ = -0,18 , р < 0,01). Цель работы – определить влияние полиморфизма гена интерлейкина-6 на эффективность противовирусной терапии больных хроническим гепатитом С. Материалы и методы. В исследование включены 83 больных хроническим гепатитом С (ХГС). Проведен анализ эффективности терапии схемой peg-IFNα + SOF + RBV в зависимости от полиморфизма гена интерлейкина-6 (rs1800795). Результаты. Установлено, что все пациенты с ХГС и генотипом СС (14 – 100%) ответили на противовирусную терапию схемой peg-IFNα + RBV + SOF, при этом среди пациентов с генотипами CG/GG ответили на лечение лишь 85,5 % (59 из 69). У больных ХГС с генотипами CG/GG, которые ответили на ПВТ формированием СВО24, негативизация HCV-RNA происходила медленнее, в отличие от пациентов с генотипом СС, у которых уже с 4 недели лечения отмечено стойкое исчезновение вируса из крови. При условии достижения СВО24 у всех пациентов с генотипом СС полиморфизма гена IL-6 в эти сроки произошла полная нормализация активности АлАТ. У большинства больных ХГС с СВО24 и CG/GG генотипами после прекращения ПВТ активность АлАТ продолжала снижаться и нормализовалась через 24 недели наблюдения у 94,9 % (56 из 59). У 20,0 % пациентов, которые не ответили формированием СВО24 и имели генотип CG/GG, на момент оценки СВО24 активность АлАТ в сыворотке крови оставалась повышенной. Для определения факторов, которые имеют статистически значимое влияние на результаты ПВТ по схеме peg- IFNα + RBV + SOF, проведена ранговая корреляция по Кенделлу. Полиморфизм гена IL-6 имел влияние на эффективность ПВТ: как на негативацию HCV-RNA в крови на момент завершения лечения (р = 0,04), так и на достижение СВО24 (р = 0,03). Отсутствие формирования ответа на момент завершения ПВТ, а также отсутствие формирования СВО12 и СВО24 ассоциировались с наличием генотипов CG/GG полиморфизма гена IL-6 и более высоким показателем активности АлАТ в начале проведения ПВТ(τ = -0,18, р < 0,01). Выводы. У больных ХГС генотип СС гена IL-6 (rs1800795) является прогностически благоприятным фактором формирования СВО 24 при проведении ПВТ по схеме peg-IFNα + RBV + SOF. Пациенты, которые не ответили на лечение формированием СВО24, имели лишь генотипыCG/GG полиморфизма гена IL-6. Даже у больных ХГС с генотипами CG/GG, которые ответили на ПВТ формированием СВО24, негативация HCV-RNA в крови происходила медленнее, в отличие от пациентов с генотипом СС. Отсутствие формирования ответа на момент завершения ПВТ, а также отсутствие СВО 12 и СВО 24 ассоциировались с наличием генотипов CG/GG полиморфизма гена IL-6 и более высоким уровнем активности АлАТ до начала проведения ПВТ (τ = -0,18, р < 0,01).
Вплив поліморфізму гена інтерлейкіна-6 на ефективність противірусного лікування хворих на хронічний гепатит С
Влияние полиморфизма гена интерлейкина-6 на эффективность противовирусного лечения больных хроническим гепатитом С
Keywords: chronic hepatitis C; interleukin-6; genetic polymorphism; antiviral agents; хронічний гепатит С; поліморфізм генетичний; інтерлейкін-6; противірусні засоби; хронический гепатит С; полиморфизм генетический; интерлейкин-6; противовирусные средства